2008
DOI: 10.1021/jf0730789
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Conjugated Linoleic Acid by Human-Derived Bifidobacterium breve LMC 017: Utilization as a Functional Starter Culture for Milk Fermentation

Abstract: This study was performed to discover bifidobacteria isolated from human intestines that optimally convert linoleic acid (LA) to conjugated linoleic acid (CLA) and to optimize the culture conditions of milk fermentation. One hundred and fifty neonatal bifidobacteria were screened for CLA-producing ability, and Bifidobacterium breve LMC 017 was selected as it showed about 90% conversion of free LA in MRS broth. The selected strain showed resistance at 0.5% LA in microaerophillic conditions. When monolinolein (LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
(32 reference statements)
2
36
0
1
Order By: Relevance
“…Barrett et al (2007) tested 18 human feces bifidobacterial strains for CLA biosynthesis with variation (2.60-76.65%) in total CLA production. Chung et al (2008) …”
Section: Uv-based Spectrophotometric Screening For Cla Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrett et al (2007) tested 18 human feces bifidobacterial strains for CLA biosynthesis with variation (2.60-76.65%) in total CLA production. Chung et al (2008) …”
Section: Uv-based Spectrophotometric Screening For Cla Productionmentioning
confidence: 99%
“…However, a normal diet (36-440 mg/day) is far lower for desired beneficial effects (Nunes and Torres 2010), and human system is totally inefficient to synthesize them de novo (Chung et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of probiotics and yogurt starter cultures led to higher concentrations of CLA than those obtained without probiotic cultures. It has been also found that the addition of monolinolein favors the production of CLA in milks fermented with B. breve LMC 017 (66). Moreover, the fatty acid profile of yogurts fermented with S. thermophilus and L. delbrueckii ssp.…”
Section: Cla In Fermented Milksmentioning
confidence: 91%
“…Studies have shown that strains of B. breve could be used as starter cultures for the development of functional milk products with high concentrations of bioactive lipids such as CLA (61)(62)(63)(64)(65)(66). Conversions of linoleic acid into CLA up to 74% were obtained using three strains of B. breve (ZL12-28, 29M2 and M7-70) isolated from breast milk (62).…”
Section: Fermentationmentioning
confidence: 99%
“…So, microorganisms isolated from dairy products, human and animal intestine were demonstrated as CLA-producing bacteria, including lactic acid bacteria (LAB) and bifidobacteria. At the present, Lactobacillus reuteri, Lactobacillus rhamnosus, Lactobacillus plantarum; Lactobacillus brevis, Lactobacillus acidophilus; Lactococcus lactis, Propionibaterium freudenrehichii, Bifidobacterium sp, Streptococcus, among others, were able to form CLA [52][53][54].…”
Section: Bacterial Cla and Clna Productionmentioning
confidence: 97%